Analysis of incidence and prognostic significance FLT3, c-KIT and NPM1 genes mutation in children with acute myeloid leukemia - L. V. Guk; T. V. Savitskaya; D. A. Domninsky; V. O. Bobrinina; M. M. Schneider; A. A. Maschan; O. V. Aleinikova (Онкогематология, 2022)
Prognosis of patients with acute myeloid leukemia receiving intensive chemotherapy is defined as kariotyping anomalies, and mutations of genes responsible for surviving and self-maintenance leukemic cells. In the giving work incidence of mutation involving genes FLT3, c-KIT, NPM1 having prognostic value in adults is analysed. Kynase domain FLT3 mutation in 18 from 83 patients (21.6%) was detected. 2 from 18 patients (11%) achieved complete remission, 5 from 18 patients (27.7%) with FLT3 mutations were refractory to therapy, two patients died from treatment complications, 9 from 18 (50%) relapsed. Only 2 patients (11%) are alive in continuous complete remission. с-KIT mutations detected in 14.2% (2/14 patients), and NPM1 mutations represented allelic polymorphism. Thus, kynase domain FLT3 mutation are prognostic unfavorable.